Evaluating the effect of different modified microplastics on the availability of polycyclic aromatic hydrocarbons - Li, Zhiwei; Hu, Xialin; Qin, Lanxue; Yin, Daqiang (Water research (Oxford), 2020)
Microplastics (MPs) discharged into the natural environment undergo various wearthering pathways, such as mechanical abrasion and ultraviolet (UV) irradiation. However, little is known about the effects of such aged MPs on the bioavailability of hydrophobic organic compounds (HOCs) in aqueous environments. To simulate the natural oxidation and UV-ageing process of MPs, three kinds of modified polyethylene MPs were obtained by plastic etching processes common in industry and UV irradiation, namely, etched MPs (EMPs), UV-aged MPs (UV-MPs), and etched MPs followed by UV ageing (UV-EMPs). The modified MPs showed a higher content of surface oxygen-containing groups than the pristine MPs, and the specific surface area and pore volume increased significantly after etching and ultraviolet ageing, especially for the EMPs (1.67 m2 g−1 and 0.0049 cm³ g−1) and UV-EMPs (2.37 m2 g−1 and 0.0089 cm³ g−1). The effect of modified MPs on the availability of 10 polycyclic aromatic hydrocarbons (PAHs, logKow 4.18–6.20) was evaluated by negligible-depletion solid-phase microextraction (nd-SPME). The free concentrations (Cfree) of most PAHs (except for less hydrophobic PAHs, logKow 4.18 and 4.56) decreased with an increasing concentration of MPs. The logarithms of the sorption coefficients of PAHs with various MPs (logKMPs, logKUV-MPs, logKEMPs and logKUV-EMPs) were linearly correlated with logKow, suggesting that the sorption is hydrophobicity dependent. Compared with the results for pristine MPs (logKMP 3.80–4.95), UV ageing only slightly enhanced the sorption of PAHs by MPs (logKUV-MPs 3.71–4.98), whereas the plastic etching processes significantly enhanced sorption (logKEMPs 3.85–5.18 and logKUV-EMPs 3.90–5.28). The sorption of PAHs to MPs is mainly based on partitioning; however, a mechanism of adsorption also likely takes place in EMPs and UV-EMPs due to hydrogen bonding and π-π interactions. Desorption study indicated that PAH desorption from MPs are dominated by film diffusion. However, intraparticle diffusion also takes great part for the EMPs. These results suggest that modification of MPs in the natural environment will change the availability of HOCs. [Display omitted] •MP properties changed more obviously by etching modification than by UV irradiation.•The availability of PAHs in modified MPs were investigated by negligible-depletion SPME.•UV aging only slightly enhanced the sorption of PAHs by MPs.•Plastic etching processes significantly enhanced PAH sorption by MPs.•Both partitioning and adsorption are responsible for PAH sorption to the etched MPs.